Geophysical monitoring at the Ketzin pilot site for CO2 storage: New insights into the plume evolution - Ivandic, M.; Juhlin, Christopher; Lüth, S.; Bergmann, P.; Kashubin, A.; Sopher, D.; Ivanova, A.; Baumann, G.; Henninges, J. (Elsevier Ltd, 2015)
© 2014 Elsevier Ltd. To date, 3D time-lapse seismic monitoring at the Ketzin CO2 storage pilot site comprised a baseline survey conducted in 2005 and two repeat surveys conducted in 2009 and 2012. At the time of the first repeat survey (22-25kt of CO2), the CO2 plume was found to be concentrated around the injection well with a maximum lateral extent of approximately 300-400m and a thickness of 5-20m. Data from the 2012 survey (61kt of CO2), show further growth and migration of the amplitude anomaly interpreted to be induced by the CO2 injection. The anomaly is similar in shape to that obtained from the 2009 survey, but significantly stronger and larger by ~150m in the N-S direction and by ~200m in the E-W direction. In agreement with the 2009 survey, the new data show a westward propagation of the plume, a trend governed by the complex structure of the reservoir. No evidence of systematic changes in the seismic signature within the overburden is observed. A quantitative assessment of the plume reveals a 15% discrepancy with the injected amount, which could be attributed to the ongoing dissolution processes. However, the estimated quantity also contains significant uncertainty.